Tantangan dan Strategi bagi Guru dalam Menerapkan Pendidikan Jasmani Inklusif: Tinjauan Sistematis - Husain, Andi Baso; A. Anwar Ishar (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
Purpose: Inclusive Physical Education (PE) aims to ensure equitable participation for all students, including those with disabilities. However, school implementation is often hindered by structural, pedagogical, and social barriers. This systematic review synthesizes empirical studies published between 2010 and 2025 to identify challenges and strategies in implementing inclusive PE. Methods: Literature searches were conducted through Scopus, Web of Science, PubMed, and Google Scholar using PRISMA guidelines. Inclusion criteria encompassed empirical studies on challenges and strategies for inclusive PE implementation in school settings. Study identification, selection, and data extraction were performed by two independent reviewers. Seventy-two eligible studies were analyzed through thematic synthesis to identify patterns and common themes. Results: Analysis identified four main challenge domains: (1) limited teacher competence and training, (2) non-adaptive facilities, (3) rigid curricula, and (4) social stigma toward students with special needs. Effective strategies reported include continuous professional development for teachers, collaborative teaching, task differentiation, and implementation of Universal Design for Learning (UDL). Findings also highlight the importance of management support and parental involvement in strengthening school inclusion. Conclusion: Effective implementation of inclusive PE requires multi-stakeholder collaboration and context-based policy reforms to strengthen teachers' capacities and promote sustainable school inclusion.